A Pilot Binational Study of Health Behaviors and Immigration - Hennessy-Burt, Tamara E. (Springer US, 2010)
In the US, Mexican immigrant women often have better health outcomes than non-Hispanic white women despite a greater health risk profile. This cross-sectional pilot study compared women living in Chavinda, Michoacán (n = 102) to women who had migrated from Mexico to Madera, California (n = 93). The interview gathered information on acculturation and risk behaviors including smoking, alcohol use and number of sexual partners. The results suggest that more acculturated women living in the US are more likely to consume alcohol. US residence and higher acculturation level was marginally associated with having more than one sexual partner. There were no differences between odds of smoking among Chavinda and Madera women. While results with acculturation are not consistently significant due to small sample sizes, the results are suggestive that acculturation among immigrant Hispanic women in the US may be associated with adverse health behaviors, and selective migration seems less likely to account for these differences.